Sistem Pemantauan Tingkat Kandungan Air Tanah dan Kendali Pompa Penyiraman Otomatis pada Tanaman Strawberry - Hadian Hadian; Asep Ririh Riswaya; Heri Wahyudi (Jurnal Computech & Bisnis (e-journal), 2022)
The writing of this paper discusses the process of monitoring strawberry plants implemented in strawberry gardens which will later become a reference to be able to design a tool for monitoring strawberry plants through Internet of Things (IoT) technology. There are several tools used, one of which is Arduino IDE as programming software to connect the Esp 8266 MCU Node, DHT 22 Sensor. Soil moisture Sensor, and other electronic components. Some of these tools are programmed using Eagle Software as a hardware board printing to form a PCB (Printed Circuit Board) or printed circuit board and become an interconnected hardware device. The use of the Bylink Application as its control and monitoring. Empirically and according to several farmers in Ciwidey, Bandung Regency, strawberry is a plant that is susceptible to changes in temperature and climate. With this tool, it is hoped that it will make it easier for farmers to determine soil moisture, identify plants that have not been watered and have not been given anti-pests or vitamins, and that their use can be extended both on a small scale in plantations to large scale that is able to take advantage of several agricultural industries. In addition, this system can be a modern digital technology that is able to reduce the percentage of crop failure due to lack of air or exposure to pests and temperature changes so that growing strawberries is easier and more efficient.